2D LDH-MoS2 clay nanosheets: synthesis, catalase-mimic capacity, and imaging-guided tumor photo-therapy - Jiayan Zhao; Hang Wu; Jiulong Zhao; Yichen Yin; Zhilun Zhang; Shige Wang; Kun Lin (Journal of Nanobiotechnology, 2021)
Abstract Owing to the hypoxia status of the tumor, the reactive oxygen species (ROS) production during photodynamic therapy (PDT) of the tumor is less efficient. Herein, a facile method which involves the synthesis of Mg–Mn–Al layered double hydroxides (LDH) clay with MoS2 doping in the surface and anionic layer space of LDH was presented, to integrate the photo-thermal effect of MoS2 and imaging and catalytic functions of Mg–Mn–Al LDH. The designed LDH-MoS2 (LMM) clay composite was further surface-coated with bovine serum albumin (BSA) to maintain the colloidal stability of LMM in physiological environment. A photosensitizer, chlorin e6 (Ce6), was absorbed at the surface and anionic layer space of LMM@BSA. In the LMM formulation, the magnetic resonance imaging of Mg–Mn–Al LDH was enhanced thanks to the reduced and acid microenvironment of the tumor. Notably, the ROS production and PDT efficiency of Ce6 were significantly improved, because LMM@BSA could catalyze the decomposing of the overexpressed H2O2 in tumors to produce oxygen. The biocompatible LMM@BSA that played the synergism with tumor microenvironment is a promising candidate for the effective treatment of cancer.